Incidence of Hypocalcaemia in Term Jaundiced Infants after Phototherapy - Farrukh Saeed, Irfan Ashraf, Sikandar Hayat, Mah Rukh, (Pakistan Journal of Medical & Health Sciences, 2022)
Jaundice is one of the main problems in the neonates early in life having an impact on around 60% of full term and 80% of premature infants. Current worldwide date reports that annually, almost 1.1 million neonates go on to suffer from serious neonatal jaundice and large amount of those reside in sub-Saharan Africa and South Asia. The goal of our research is to quantify the incidence of hypocalcaemia in term infants with hyperbilirubinemia who have been treated with phototherapy for 48 hours. Objective And Methodology: This research makes use of a descriptive case series study approach. Data collection was done in the Pediatrics unit 1 services hospital Lahore from six months from Jan, 2022 to July 2022. Patients' basic information (such as their names, ages, sexes, and addresses) was collected during the Study's case registration process. Newborns that met the study's eligibility criteria were given 48 hours of laser treatment. After 48 hours of laser treatment, the serum calcium level was checked and recorded. Results: The average age of the neonates was 8.83±3.99 days. The average birth weights of the newborns were 2.28±0.39 kg. The mean Serum Calcium level at Baseline was 9.33±1.09 mg/dl. The mean Serum Calcium level after 48 hours of laser therapy was 7.64±1.36 mg/dl. There were 30(34.5%) neonates with hypocalcemia and 57(65.5%) neonates without hypocalcaemia in this study. Conclusion: The frequency of hypocalcaemia was moderate 34.5% among neonates with hyperbilirubinemia who received laser therapy. Keywords: Hypocalcaemia, Jaundice, Hyperbilirubinemia, Laser Therapy, Neonatal Jaundice